2010
DOI: 10.1248/bpb.33.1242
|View full text |Cite
|
Sign up to set email alerts
|

Melanogenesis Inhibitory Effect of Fatty Acid Alkyl Esters Isolated from Oxalis triangularis

Abstract: Oxalis triangularis (purple shamrock or purple clover) in the family Oxalidaceae is an edible perennial plant that is easily cultivated. The leaves of Oxalis triangularis are especially appreciated due to their sour and exotic taste. Oxalis triangularis has intensely purple leaves with a monomeric anthocyanin content of 195 mg/100 g on a malvidin 3,5-diglucoside basis, which makes them a potential source of natural colorants.1) Additionally, it is known that treatment with the flavones, C-glycosides, as copigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Repeated column chromatography of the EtOAc fraction through silica gel resulted in the isolation of eight constituents ( Figure 2): p-hydroxybenzoic acid (1) 14 , methyl p-hydroxybenzoate (2) 15 , vanillic acid (3) 16 , methyl vanillate (4) 17 , syringic acid (5) 18 , β-sitosterol (6) 19 , α-amyrin acetate (7) 20 , and ethyl linoleate (8) 21 . Compounds 1-5 were all p-hydroxybenzoic acid derivatives, which were fully identified by spectroscopic methods, including 1 H and 13 C NMR data.…”
Section: Resultsmentioning
confidence: 99%
“…Repeated column chromatography of the EtOAc fraction through silica gel resulted in the isolation of eight constituents ( Figure 2): p-hydroxybenzoic acid (1) 14 , methyl p-hydroxybenzoate (2) 15 , vanillic acid (3) 16 , methyl vanillate (4) 17 , syringic acid (5) 18 , β-sitosterol (6) 19 , α-amyrin acetate (7) 20 , and ethyl linoleate (8) 21 . Compounds 1-5 were all p-hydroxybenzoic acid derivatives, which were fully identified by spectroscopic methods, including 1 H and 13 C NMR data.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Huh et al . found that the methyl/ethyl linoenate (Figure 7c) from Oxalis triangularis exhibited melanogenesis inhibition, which was also mediated by a reduction in the cAMP level in cells [74]. …”
Section: Natural Melanogenesis Inhibitors Acting Through the Down-mentioning
confidence: 99%
“…Methyl palmitate has been shown to reduce chemical-induced hepatotoxicity in rats [ 27 ], and inhibit phagocytosis and the release of pro-inflammatory mediators in primary rat Kupffer cells [ 28 ]. Methyl linolenate significantly blocks melanogenesis and inhibits tyrosinase activity in mouse B16 melanoma cells [ 29 ]. However, to date, there are no published reports of the anti-inflammatory properties of fatty acid acyl esters.…”
Section: Resultsmentioning
confidence: 99%